Utility of satellite imagery in estimating coastal marine water attributes - Majid, Abdul; Ikhsan, Natrah; Hassan, Zafri (Elsevier, 2025)
Coastal water resources are essential for sustaining biodiversity and community well-being, yet rapid population growth and climate change increasingly threaten their sustainability. Satellite remote sensing has emerged as a powerful tool for monitoring coastal water quality due to its extensive spatial coverage, cost effectiveness, and rapid data acquisition. The scientific community has seen considerable advances in recent years through these technologies. In view of these developments, this study presents a scoping review of 465 peer-reviewed journal articles published between 2019 and 2024, sourced from Scopus. The analysis identifies commonly used satellite platforms for assessing five critical water quality parameters chlorophyll-a (Chl-a), temperature, colored dissolved organic matter (CDOM), pH, and phosphate across predefined climatic zones and water types. We further examine prevalent algorithmic approaches and validation metrics. Findings indicate that most studies rely on data from Aqua, Sentinel, and Landsat satellites. Results also reveal that Chl-a and temperature are the most widely measured parameters, particularly in temperate and subtropical marine waters, whereas Arctic regions and freshwater systems remain understudied. Recent trends show a growing reliance on empirical and machine learning based algorithms, with root mean square error (RMSE) and coefficient of determination (R2) as the most common validation metrics. These results highlight the need for standardized validation protocols and expanded research efforts in underrepresented regions and parameters to enhance global water quality monitoring.